Secondary Data Analysis of Postmortem Records in PCMC Area to Understand the Burden of Myocardial Infarction - Sharma Dharmendra; Sinnarkar Vineet V.; Suryawanshi Sailee S.; Sonawane Milind V. (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: There has been a global upsurge in the cases of non-communicable diseases, especially cardiovasculardiseases. Analysis of the leading causes of death in the community is very crucial in understanding and planningthe health care policies. The aim of this study was to evaluate the burden of myocardial infarction in PimpriChinchwad city with the help of the Postmortem examination record analysis.Methods: In this cross sectional study, the data related to 674 deaths in the period of 2019 to mid-2021 wasconsidered. The data was obtained from the postmortem examination records of the Postmortem Centre ofTalegaon Dabhade General Hospital. The obtained data was classified and analyzed with the help of descriptivestatistics in order to find the burden of the leading causes of death, especially of myocardial infarction.Conclusion: Myocardial Infarction was found to be the leading cause of death in the Pimpri Chinchwad arearanging to 33.38%. It was also seen that the deaths due to myocardial infarction was seen more in people of the agegroups 25 to 64 years. These can be prevented by changing lifestyle, diet and reducing risk factors like smoking,obesity and stress. The obtained result also indicates that there is a need for increased cardiac care facilities withmore cardiac ambulance and cardiac care centres in Pimpri Chinchwad city. The other leading causes of deathfound in the secondary analysis of the Postmortem records were death due to head injury (n= 142, 21.06%) andhaemorrhagic shock (n=70, 10.38%).